ANALISIS ISI KONTEN EDUKASI INSTAGRAM @CFDS_UGM DALAM MEMBANTU LITERASI DIGITAL FOLLOWERS - Rochani, Firyal Rania; Maserona Sarungu, Lukas (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
This research analyzes the educational content of the Instagram account @cfds_ugm, managed by the Center for Digital Society (CfDS) at Gadjah Mada University, to understand its role in enhancing the digital literacy of its followers. The study was conducted due to the low level of digital literacy in Indonesia, while the use of social media platforms like Instagram is very high. Using a qualitative approach and content analysis method, data was collected through documentation of @cfds_ugm's content and analyzed based on Doug Belshaw's eight elements of digital literacy: cultural, cognitive, constructive, communicative, creative, critical, confident, and civic. The results show that @cfds_ugm's content successfully integrates all elements of digital literacy, not only providing technical information but also encouraging critical awareness, social responsibility, and active participation in the use of digital media. These findings indicate that educational content on social media can be an effective tool fooving digital literacy in society.